Tumor estromal gastrointestinal (TEGI): estudo morfológico e imunohistoquímico de dez casos. - Hirata, L.; Schmitt, F. C. (My University, 1991)
To study the histogenesis of spindle and epithelioid cell tumors of gastrointestinal tract we evaluated ten cases of gastrointestinal stromal tumors (GIST) previously classified as leiomyomas (6 cases) and leiomyosarcomas (4 cases). The cases were studied by morphological and immunohistochemistry procedures with search of three markers: muscle specific actin (HHF-35), vimentin and S-100 protein. All tumors showed vimentin positivity. Muscle differentiation was demonstrated in three cases (33.3%), all of them benign. One tumor, in small intestine, displayed S-100 protein positivity. The results showed that the GIST represent a heterogeneous group of tumors, most of which consist of primitive mesenchymal cells.
Gastrointestinal stromal tumor (GIST): morphologic and immunohistochemical study of 10 cases
Keywords: tumor marker; chemistry; gastrointestinal tumor; human; immunohistochemistry; leiomyoma; leiomyosarcoma; retrospective study; ultrastructure; English Abstract; Gastrointestinal Neoplasms; Human; Immunohistochemistry; Leiomyoma; Leiomyosarcoma; Retrospective Studies; Tumor Markers, Biological